Interventions to Reduce the Development of Suicidal Ideations in College Students - Tri Karizma; Aat Sriati; Furkon Nurhakim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to map interventions that can reduce the development of suicidal ideation in college students. The method used is scoping review using PRISMA 2020 in study selection and a literature search strategy using the PCC format. The databases used are EBSCO, PubMed, and Garuda. Article quality is assessed using JBI critical appraisal tools. The research results are interventions to reduce the development of suicidal ideation in students, namely Cognitive Therapy, Collaborative Assessment and Management of Suicidality (CAMS), Dialectical Behavior Therapy (DBT) both individually and in groups, and campaigns for social norms. In conclusion, it is essential to maintain psychological health to prevent it from developing into a suicide attempt which is vital to be aware of by individuals and the environment. Appropriate intervention can affect the development of these suicidal ideations. Keywords: Suicide Idea, Intervention, Students